Exploring and investigating the status, implementation and problems /barriers in implementation of KOHA at libraries of Pakistan - Ahmed Noor, Shabana (Journal of Quranic and Social Studies, 2022)
The study of exploring and investigating the status, implementation and problems / barriers in implementation of KOHA software at libraries of Pakistan has been carried out in the eleven institute where KOHA is functional. These institute are selected based on purposive sampling procedure and data has been collected from 122 participants of the selected institutes. Three types of institutes have been observed i.e., universities, college and other public libraries. Based on the findings of the study it has been concluded that, the current status of library automation in Pakistan the key factors are cost of library automation system, display and screen and maintenance cost. Regarding the implementation of Koha in Pakistan key factors are founded librarians training on ILMS skills and latest information technology and ability of Koha OSS to save library budget. By observing the key problems/barriers involved in the implementation of Koha in Pakistani libraries. The network configuration, erratic power supply and lack of knowledge about operating system are founded the key problems/barriers involved in the implementation of Koha in Pakistani libraries..com